Impact of Oxycodone HCl Extended-release Formulary Restrictions on Extended-release Opioid Market Share, Healthcare Resource Utilization and Costs in Commercial and Medicare Plans - Rolin L. Wade; Chi-Chang Chen; Ajita P. De; Jaren C. Howard (Journal of Health Economics and Outcomes Research)
**Background:** Previous research demonstrated that utilization management (UM) such as prior authorization (PA) or non-formulary (NF) restrictions may reduce pharmacy costs when designed and applied appropriately to certain drug classes. However, such access barriers may also have unintended consequences. Few studies systemically analyzed the impact of major UM strategies to extended-release (ER) opioids on different types of health plans.